A new report of moss-camouflaging mantis Nanomantinae in Bali, Indonesia - Sudiarta, I Putu; Wirya, Gusti Ngurah Alit Susanta; Selangga, Dewa Gede Wiryangga; Sanjaya, I Gusti Ngurah Prabu Wira; Arimbawa, I Made; Damastra, Garda Bagus (Universitas Lampung, 2023)
In 2019 we found moss praying mantis around the forest in the Bedugul Area of Bali, Indonesia. This species belongs to the family Mantidae, subfamily Nanomantinae, and predicted as member of Calofulcinia genus based on diagnostics of morphological characteristics, behavior, and habitat. Information about the morphological characteristics and data from the molecular sequencing database of the genus Calofulcinia has been very limited. In this research, the barcoding DNA of mitochondrial Cytochrome Oxidase I (mtCOI) of the species is noted using paired primers LCO1490 and HCO2198. Based on the sequence analysis (identity matrix and phylogeny analysis), the moss mantis from Bali has low similarity and genetic relationship with other Mantodea species from GenBank database. The data indicate the moss mantis from Bali has not been reported previously. In addition, the distribution of moss mantis species in Bedugul, Bali, Indonesia has just been described and recorded.